Obraz Sokratesa jako nauczyciela w tekstach starożytnych - Taboł, Sebastian (Acta Universitatis Nicolai Copernici Pedagogika, 2015)
An image of Socrates as a teacher in ancient texts The article presents the image of Socrates as a teacher, which runs through the ancient books. The author of no wonder that the image is authentic and which is false. Have been analyzed texts of Aristophanes, Xenophon, Plato and Diogenes Laertius and Aristotle. The account shows a positive image of the philosopher. Only Aristophanes in the Clouds was released it in a satirical way. Although Socrates objected to calling him a teacher, but by educating the youth of Athens and he was and could become a model for today’s teachers. Due to the limited volume, which has a product image included in the dialogues of Plato Socrates was only signaled because of the multitude of dialogues, which would be analyzed.